Transformation of Hadith Study in the Digital Era: an Effectiveness of Hadith Applications and Websites - Najiyah, Nur Laili Nabilah Nazahah; Putriani, Rizki (Universitas Islam Negeri Imam Bonjol Padang, 2024)
In today's digital age, the availability of hadith software and websites like maktabah syamilah, gawāmi' al-kalīm, lidwa pusaka, dorar.net, carihadis.com, sunnah.one plays a crucial role in the study of hadith. However, these platforms have some limitations, such as issues with numbering hadiths, copyright concerns, and restricted accessibility. This article aims to explore the impact of technology on the study of hadith, specifically by examining the introduction of applications and websites designed to facilitate user experience, particularly for hadith scholars and researchers. This study adopted qualitative research methods, employing a process that involved three concurrent stages of analysis: condensing data, presenting findings, and drawing conclusions. Out of the six analysed hadith softwares, gawāmi' al-kalīm and dorar.net were found to have user-friendly interfaces, especially for conducting hadith takhrij. Nonetheless, both platforms have their drawbacks, such as the absence of details regarding the authenticity of a hadith on dorar.net and the exclusive use of Arabic in the Gawāmi' al-Kalīm app, along with occasional data inaccuracies. Despite these limitations, users can alleviate them by exploring alternative software options or resorting to traditional hadith sources containing the necessary information.